Pengaruh Kohesivitas dan Kepuasan Kerja terhadap Turnover Intention Karyawan - Novia Annisa Putri; Nurmala Katrina Pandjaitan; Sadikin Kuswanto (IPB University, 2018)
PT X is a major regional pharmaceutical company that develops and markets innovative products in Indonesia and other countries in South-East Asia. The high turnover rate in PT X indicates a further need to be explored about this condition and see if it is affected by employee cohesiveness and job satisfaction. This study uses quantitative approach with questionnaires that distributed to 120 head office employees with convenience sampling method. The result of structural equation modeling analysis shows that the better employee cohesiveness will increase the job satisfaction so that it can decrease the employee's desire to resign from the company. Cohesiveness has a significant positive effect on job satisfaction. In this case cohesiveness plays an important role in improving job satisfaction because having a cohesive group will affect employee satisfaction. Cohesiveness and job satisfaction have a significant negative impact on turnover intention. This suggests that cohesiveness and job satisfaction play an important role in decreasing employee intent turnover, even though the effect of cohesiveness is less than the effect of job satisfaction on turnover intention.